A New Efficient Method for Solving Two-Dimensional Nonlinear System of Burger’s Differential Equations - Shams A. Ahmed; Mohamed Elbadri; Mohamed Z. Mohamed (Abstract and Applied Analysis)
In this work, the Sumudu decomposition method (SDM) is utilized to obtain the approximate solution of two-dimensional nonlinear system of Burger’s differential equations. This method is considered to be an effective tool in solving many problems. Our results have shown that the SDM offers a much better approximation for solving several numbers of systems of two-dimensional nonlinear Burger’s differential equations. To clarify the facility and accuracy of the strategy, two examples are provided.